PEMBELAAN DIRI DALAM PERKARA PIDANA DITINJAU BERDASARKAN PASAL 49 KUHP - Fatma Fauzia (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractEvery person who commits a criminal offense and is threatened with a criminal offense by law because of a forced defense (noodwere) caused by an attack or a threat of a very close attack at that time that is against the law is not in the criminal offense. And every person who makes a forced defense that exceeds the limit (noodwere exces) which is directly caused by the shock of the soul because of an attack or threat of the attack, is not convicted. Regarding the defense carried out by someone in a situation which is very compelling so that it can become a reason for criminal offense as described above, it is regulated in Article 49 of the Criminal Code. As in Article 49 Paragraph (1) concerning forced defense, to find out whether an act is a defense or vice versa, it is not explained how to make a permissible defense. Likewise Article 49 Paragraph (2) concerning forced defenses that exceed the limits does not explain the exceeding allowed limits. The problem raised in this paper is how to apply the rules of self-defense in criminal cases in Article 49 paragraph (1) and paragraph (2) of the Criminal Code. This type of research used is normative legal research, namely library research with the problem approach used in writing this thesis is the statute approach. The results showed that the application of self-defense rules was appropriate, because it was in accordance with the elements of the conditions in making a forced defense or forced defense that exceeds the limit